A Study Of Stylistic Devices Used In “Số Đỏ” By Vũ Trọng Phụng And In “Dumb Luck” As Its English Translational Equivalent - Đỗ Thị Quý (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Stylistic devices have a great power of expressive meaning in literature. There are many different kinds of stylistic devices and each kind of them brings different effects. This thesis is carried out to investigate the stylistic devices used in “Số Đỏ” by Vũ Trọng Phụng and in “Dumb Luck” as its English translational equivalent by Peter Zinoman and Nguyen Nguyet Cam. The study carries out 120 samples in Vietnamese and 120 samples in English. The qualitative, quantitative, descriptive and comparative methods are used to achieve the aims and objectives of the study. Thanks to the combination of these methods, the data are collected, described and compared to find out how the stylistic devices in “Số Đỏ” by Vũ Trọng Phụng are transferred in the English translational equivalent “Dumb Luck” by Zinoman and Nguyet Nguyet Cam. Hopefully, the study could help the readers understand more clearly about stylistic devices in “Số Đỏ” and in its English translational equivalent, as well as help teachers, learners and trans